Oral Administration of Lactobacillus Inhibits the Permeability of Blood-Brain and Gut Barriers in a Parkinsonism Model - Angélica Y. Nápoles-Medina; Blanca R. Aguilar-Uscanga; Josué R. Solís-Pacheco; Aldo R. Tejeda-Martínez; Luis J. Ramírez-Jirano; María F. Urmeneta-Ortiz; Veronica Chaparro-Huerta; Mario E. Flores-Soto (Behavioural Neurology)
It has recently been shown that the administration of probiotics can modulate the microbiota-gut-brain axis and may have favorable effects in models of Parkinson’s disease. In this study, we used a hemiparkinsonism model induced by the neurotoxin 6-OHDA to evaluate the efficacy of the administration of a four-week administration of a mixture containing the microorganisms Lactobacillus fermentum LH01, Lactobacillus reuteri LH03, and Lactobacillus plantarum LH05. The hemiparkinsonism model induced an increase in rotations in the apomorphine test, along with a decrease in the latency time to fall in the rotarod test on days 14 and 21 after surgery, respectively. The administration of probiotics was sufficient to improve this condition. The model also showed a decrease in tyrosine hydroxylase immunoreactivity in the striatum and the number of labeled cells in the substantia nigra, both of which were counteracted by the administration of probiotics. The permeability of the blood-brain barrier was increased in the model, but this effect was reversed by the probiotics for both brain regions. The gut barrier was permeated with the model, and this effect was reversed and dropped to lower levels than the control group after the administration of probiotics. Finally, lipid peroxidation showed a pattern of differences similar to that of permeabilities. The inhibition of the permeability of the blood-brain and gut barriers mediated by the administration of probiotics will likely provide protection by downregulating oxidative stress, thus affecting the rotarod test performance.